ANALISIS PERBEDAAN PEMAHAMAN MASYARAKAT TENTANG DESA TANGGUH BENCANA (DESTANA) DI DESA TAMBAKREJO KABUPATEN BLITAR JAWA TIMUR - Yulis Bigandata; Susiani Endarwati; Purbudi Wahyuni; Yohana Noradika Maharani (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2023)
Indonesia is located on the meeting point of three continent pieces namely Indo-Australia, Eurasia, and Pacific. That is why Indonesia has high risk of earthquake either low or high level. Blitar Regency is one of the areas which has risk of tsunami namely Wonotirto District, Panggungrejo District, Wates District, and Bakung District.The goal of this research is to analyze the different understanding of villagers about Disaster Sturdy Village or Desa Tanguh Bencana (Destana) in Tambakrejo Village Wonotirto District Blitar Regency. The kind of approach in this study is qualitative research with pre-experimental by using pre test-post test. The data were taken by giving questionnaire, and then they were analyzed by Wilcoxon Match Pairs Test. The result of this study shows that there are 39 respondents (54,2%) who have less understanding about Disaster Sturdy Village or Desa Tanguh Bencana (Destana) before giving infromation about Disaster Sturdy Village. After being given information about Disaster Sturdy Village, it was got 44 respondents (61.1%) who have good understanding. The result of analysis shows the significant difference namely Z result -5.468 with (σ ≤ 0.05). It means there is different understanding of the people about Disaster Sturdy Village before and after being given information.